Benzo-pyrrolidinyl substituted silicon phthalocyanines: A novel two-photon lysosomal nanoprobe for in vitro photodynamic therapy - Xiuqin Chen; Guizhi Chen; Sitong Cao; Ruoxin Ye; Ruoyi Qiu; Xiangyu Yang; Yiru Peng; Hong Sun (Photodiagnosis and Photodynamic Therapy)
Lysosomes are pivotal in diverse physiological phenomena, encompassing autophagy, apoptosis, and cellular senescence. The demand for precise tumors treatment has led to the development of specific lysosome-targeting probes capable of elucidating lysosomal dynamics and facilitating targeted cell death. In this research, we report the synthesis and characterization of a novel benzopyrrolidinyl-substituted silicon phthalocyanine (Py-SiPc), designed for selective lysosome labeling and Fluorescence imaging-guided in vitro photodynamic therapy. Furthermore, we encapsulated Py-SiPc within a biocompatible nanocarrier, dipalmitoylphosphatidylethanolamine-polyethylene glycol 2000 (DSPE), to create water-soluble nanoparticles (DSPE@Py-SiPc). These nanoparticles exhibit exceptional lysosome labeling capabilities, as evidenced by bioimaging techniques. Upon exposure to laser irradiation, DSPE@Py-SiPc efficiently induces the production of reactive oxygen species, impairing lysosomal function and triggering lysosomal-mediated cell death. The DSPE@Py-SiPc system emerges as a promising photosensitizer.